2020
DOI: 10.1021/acsaem.0c01405
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Nickel Sulfides and Their Electrocatalytic Activities for Hydrogen Evolution Reaction: A Case Study of Crystalline h-NiS and o-Ni9S8 Nanoparticles

Abstract: Electrocatalytic materials play a crucial role in the development of technologies for hydrogen production (hydrogen evolution reaction) from renewable and sustainable energy resources. Among these materials, nickel sulfides are promising catalysts due to their activity, stability, and cost-effectiveness. However, while the performance of nickel sulfides is linearly correlated to the crystalline structure, synthesis of single crystalline phases of nickel sulfides with controlled morphology is not trivial. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…22-1193), which proves the heterostructure of CoNi–S/C. 37,38 In comparison with the results of XRD patterns for CoNi–P/C and CoNi–S/C, CoNi-SP/C shows a more complicated phase structure from CoNi–S and CoNi–P as expected (Fig. 1i).…”
Section: Resultssupporting
confidence: 64%
“…22-1193), which proves the heterostructure of CoNi–S/C. 37,38 In comparison with the results of XRD patterns for CoNi–P/C and CoNi–S/C, CoNi-SP/C shows a more complicated phase structure from CoNi–S and CoNi–P as expected (Fig. 1i).…”
Section: Resultssupporting
confidence: 64%
“…However, only limited research has concentrated on HER electrocatalysis in alkaline media, with the majority of the existing research concentrating on acidic media. Crystalline nickel sulfides are particularly promising catalysts, as reported by Silva et al [ 73 ] who later found that their performance correlates to their crystalline structure. Both of the as-synthesized phases of nickel sulfide, orthorhombic (o-Ni 9 S 8 ) and hexagonal nickel sulfide (h-NiS), showed excellent HER activity in an alkaline medium, even surpassing W 2 C and Mo 2 C ( Figure 11 b).…”
Section: Ni-based Electrocatalysts For Her In Alkaline Mediummentioning
confidence: 92%
“…( b ) HER-LSV curves of o -Ni 9 S 8 and h -NiS, reprinted with permission from Ref. [ 73 ]. ( c ) HRTEM images and ( d ) HER performance of the Ni-GF/VC catalyst, reprinted with permission from Ref.…”
Section: Ni-based Electrocatalysts For Her In Alkaline Mediummentioning
confidence: 99%
“…Among numerous electrocatalysts, platinum (Pt)‐based materials are considered to be the benchmark electrocatalysts for triggering HER, however, their cost and scarcity limit the large‐scale application. Therefore, the cost‐effective electrocatalysts, including sulfides, [ 4 ] carbides, [ 5 ] nitrides, [ 6 ] chalcogenides, [ 7 ] and phosphides [ 8 ] have been widely explored as the alternatives of Pt‐based electrocatalyst. In the light of their economically advantageous and similar bond energy to that of Pt, ruthenium (Ru) has evoked much attention as a potential hydrogen evolution electrocatalyst.…”
Section: Introductionmentioning
confidence: 99%